Lower limb landing responses by young female gymnasts on different types of mats: a preliminary study - Brtva, P.; Irwin, G.; Farana, R. (ISBS Proceedings Archive (Michigan), 2022)
Landing is a fundamental skill in artistic gymnastics, practiced continually throughout all levels and using various types of landing mats. The aim of the current study was to investigate how the vertical ground reaction forces (VGRF), knee and ankle joint kinematics changes during gymnasts landing on different types of landing mats with FIG certification. Four young active female gymnasts performed 10 trials of landing to two type of mats. Synchronized kinematic and kinetic data were collected for each trial. Effect size statistics determined individual and group mean differences between landing conditions. The preliminary results of the current study suggested that the PROTOTYPE of landing mat reduces the VGRF and thus may decrease the impact forces acting on the lower limbs in gymnastics.